Firm Size, Market Risk, and Stock Return: Evidence from Indonesian Blue Chip Companies - Handayani, Meutia; Farlian, Talbani; Ardian, Ardian (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
This study examines the influence of firm size and market risk on the stock return of Indonesian high reliable companies. The samples are companies listed on the LQ45 between 2015 and 2017. There are 45 companies have been selected or 196 observations. The data was obtained from the financial reports and analysed by using regression for panel data method, namely the common effect model and the Chow test. The results demonstrate that firm size has an effect on the stocks return, while market risk does not have effect on the stocks return of the blue chip companies. The results of this study are expected to help investors in making proper investment decisions toward bluechip Indonesian companies.